Pemanfaatan Tanaman Herbal Lokal Sebagai Alternatif Antibiotik Dalam Pakan Ternak - Usu, Monalisa (Jurnal Ilmu Peternakan Indonesia, 2025)
The use of antibiotics in animal feed has long been a common practice to promote growth and prevent disease, but it poses the risk of antimicrobial resistance (AMR), which negatively affects both animal and human health. This study aimed to evaluate the effectiveness of local herbal plants as alternative antibiotics in broiler feed. The selected herbs included betel leaf (Piper betle), turmeric (Curcuma longa), and Java ginger (Curcuma xanthorrhiza). A completely randomized design (CRD) was applied with four treatments: control (without antibiotics), synthetic antibiotics, betel leaf extract, and a combination of turmeric and Java ginger extracts, each with four replications. The results showed that herbal extract treatments significantly improved body weight gain, feed conversion ratio (FCR), and reduced mortality compared to the control group. The best performance was observed in the group receiving the combination of turmeric and Java ginger, which approached the results of the synthetic antibiotic group. Microbiological analysis indicated a significant reduction in the population of Escherichia coli and Salmonella spp. in the herbal treatment groups. Phytochemical screening revealed the presence of bioactive compounds such as flavonoids, tannins, and saponins, which play roles as antibacterial and immunomodulatory agents. In conclusion, local herbal plants have great potential as natural antibiotic alternatives in livestock feed, offering competitive effectiveness and safer impacts on health and the environment. Further research is required to standardize dosage and formulation for broader implementation at the industrial scale.